I b M INTERNETPRENEURSHIP UNTUK KELOMPOK PENGRAJIN SEPATU DAN KELOMPOK USAHA KONVEKSI PUSAT INDUSTRI KECIL (PIK) KEC. MEDAN DENAI - Rini Herliani; Haryadi Haryadi (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2015)
Abstrak This researh has several objectives : ( 1 ) Small Industrial Business communities  that have a soul and a spiritof entrepreneurship , so they have knowledge and attitude  of professional and  independententrepreneurship . ( 2 ) Small Industrial Business communities to be able to Develop an Effective Promotionand expand market share and penetrate new markets , both local and international . ( 3 ) Small IndustrialBusiness Actors able to create computerized and integrated accounting system , so it can easily performmonitoring , evaluation , data collection is accurate , and current. Partners is PIK  IbM program consists of 2( two ) groups : shoes artisans and Convection Industry . To achieve the goal of Community Service so doseveral activity of  Training and Workshop on Small Business in Modern Management , DevelopmentInternetpreneurship to increase business revenue Small Indutry from e-commerce/Blog Partners , makesimple financial using Zahir Accounting software.